Epidemiology of coccidiosis in calves and control of coccidiosis using toltazuril at the time of weaning : this thesis is presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Veterinary Parasitology at Massey University, Palmerston North, New Zealand - Gaddam, Mary Jones (Massey University, 2005)
Two separate studies were conducted to investigate the impact of coccidiosis in young calves. In one study calves were reared to weaning (100kg liveweight) by feeding meal with or without monensin added. The oocyst counts were low in both groups up to weaning and there was no statistically significant (p<0.05) improvement in terms of body weight or a decline in oocyst counts in the monensin-treated group At weaning a single dose of toltrazuril (20mg/kg) was given to half the calves in both groups. A similar treatment regime was given in a second study where calves had been raised to weaning by commercial calf rearers. Half of these were treated with toltrazuril (20mg/kg) and half not. In both studies there was a statistically significant (p<0.001) reduction in oocyst counts in treated calves which remained very low for 4-5 weeks post treatment. The treatment also significantly increased (p<0.001) weight gains in treated calves by 3-5kgs at 5-6 weeks post treatment. The coccidial status of other calves on a variety of farms were also monitored including a group of organic beef farms. High oocyst counts were noted on occasions where calves were not on anti-coccidial treatment. Low oocyst counts were noted in adult cows where they were examined. The two most prevalent species overall were Eimeria zuernii (95%) and E. bovis (87%) followed by E. auburnensis (62%), E. cylindrica (42%), E. canadensis (31%), E. wyomingensis (23%), E bukidnonensis (36%), E. ellipsoidalis (24%) E. alabamensis (12%), E. brasiliensis (12%), and E. subspherica (27%). The most predominant species, measured as the most numerous oocysts overall, were E. bovis (31%) followed by E. zuernii (27%), E. auburnensis (13%), E. bukidnonensis (7%), E. cylindrica (6%), E. wyomingensis (5.3%), E. canadensis (4.4%), E. ellipsoidalis (3.3%), E. brasiliensis (1.9%), E. subspherica (1.5%), and E. alabamensis (1%). The most prevalent species were also the most pathogenic species. On many occasions calves were infected with more than one species, sometimes as many as 5-6 Eimeria species. A redescription of the 11 species of Eimeria in cattle identified from New Zealand Farms was made.
Keywords: Coccidiosis in animals; Epidemiology; Cattle diseases; Eimeria; Veterinary parasitology; New Zealand